2013
DOI: 10.1007/s10936-013-9280-4
|View full text |Cite
|
Sign up to set email alerts
|

Word Order Processing in a Second Language: From VO to OV

Abstract: Event-related potential studies on second language processing reveal that L1/L2 differences are due either to proficiency, age of acquisition or grammatical differences between L1 and L2 (Kotz in Brain Lang 109(2-3):68-74, 2009). However, the relative impact of these and other factors in second language processing is still not well understood. Here we present evidence from behavioral and ERP experiments on Basque sentence word order processing by L1Spanish-L2Basque early bilinguals (Age of Aquisition [Formula:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…For the unique head parameter (subject-object-verb (SOV) and SVO word order) condition, both groups displayed similar P600 effects, but natives showed a left parietal negativity between 300 and 500 ms, while non-natives showed a frontally distributed negativity in the same time window followed by a broad negativity between 500 and 600 ms. For the unique ergative condition, all participants showed a broadly distributed negativity, but only the natives displayed a P600. Erdocia et al ( 2014 ) also reported non-native processing of syntactic traits unique to L2 with the same type of population studied by Zawiszewski et al ( 2011 ), i.e., highly proficient, early Spanish (L1)—Basque (L2) bilinguals. With a written sentence comprehension task, they studied the processing of sentences following the canonical word order of the L2 (SOV) or a non-canonical order (OSV), both of which differed from the canonical L1 word order (SVO).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…For the unique head parameter (subject-object-verb (SOV) and SVO word order) condition, both groups displayed similar P600 effects, but natives showed a left parietal negativity between 300 and 500 ms, while non-natives showed a frontally distributed negativity in the same time window followed by a broad negativity between 500 and 600 ms. For the unique ergative condition, all participants showed a broadly distributed negativity, but only the natives displayed a P600. Erdocia et al ( 2014 ) also reported non-native processing of syntactic traits unique to L2 with the same type of population studied by Zawiszewski et al ( 2011 ), i.e., highly proficient, early Spanish (L1)—Basque (L2) bilinguals. With a written sentence comprehension task, they studied the processing of sentences following the canonical word order of the L2 (SOV) or a non-canonical order (OSV), both of which differed from the canonical L1 word order (SVO).…”
Section: Introductionmentioning
confidence: 83%
“…Conversely, other studies have shown non-native ERP patterns during L2 processing despite high proficiency (Ojima et al, 2005 ; Chen et al, 2007 ; Dowens et al, 2011 ; Pakulak and Neville, 2011 ; Zawiszewski et al, 2011 ; Erdocia et al, 2014 ). For instance, Pakulak and Neville ( 2011 ) compared the ERP responses to English phrase structure violations of English listeners and late German learners of English (AoA > 10 years old) during an auditory grammatical judgment task.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The few studies that examined how L2 learners deal with such conflicts have shown that word order differences in L1 and L2 remain difficult even at high proficiency levels and when the L2 was learned early on in life (Erdocia & Laka, 2018;Erdocia, Zawiszewski, & Laka, 2014). In both of these studies, learners' online processing signatures showed clear evidence of L1 Spanish influence on parsing L2 Basque sentences.…”
Section: Introductionmentioning
confidence: 97%
“…They, on the other hand, did not commit a systematic error in constructing sentences in Turkish (SOV language) even though their L1 follows a quite different word order (VSO). Erdocia et al (2014) underline that typological differences (e.g. VO/OV) can be a relevant influence behind L1/L2 differential features that are distinctly processed by L2 speakers due to processing strategies from native language to non-native or difficulty to acquire some divergent grammatical structures.…”
Section: Rq2 Is There L1 Interference In the Use Of Turkish Case-marmentioning
confidence: 91%